Cortical Expression of the Polysialylated Isoform of the Neural Cell Adhesion Molecule on Brain Tissue to Recognize Drug-Related Death: An Exploratory Analysis. (March 2018) - Cirielli, Vito; Cima, Luca; Chindemi, Chiara; Danzi, Olivia; Ghimenton, Claudio; Eccher, Albino; Mauriello, Silvestro; Bortolotti, Federica; De Leo, Domenico; Brunelli, Matteo; Tagliaro, Franco
Abstract : Abstract: The polysialylated isoform of the neural cell adhesion molecule (PSA-NCAM) has been shown to be a key player in neuroplastic changes and is expressed in various disorders. We investigated the PSA-NCAM expression on brain cortical tissue in a cohort of drug-related deaths. Brains from 25 drug abusers and 10 control subjects were removed at autopsy, and 2 samples of the right parietal lobe of each case were obtained. The polysialylated isoform of NCAM was evaluated on formalin-fixed and paraffin-embedded tissues. Eleven patients were polydrug abusers; 14 used a single substance. The mechanisms of death were acute respiratory failure (n = 19), cardiorespiratory failure (n = 4), acute heart failure (n = 1), and brain injury (n = 1). Toxicological analyses of blood were available for all cases, and urine and bile analyses for 19 of 25 cases. The polysialylated isoform of NCAM immunoexpression in the neuronal soma and dendritic spines was observed in 18 (72%) of 25 drug abusers and in 2 (20%) of 10 control subjects. Drug abusers were statistically more positive for PSA-NCAM than control subjects ( P = 0.0082). The expression of PSA-NCAM in the parietal cortex could be an indicator of brain damage due to drug abuse, and its availability could allow the forensic pathologists to develop rapid and low-cost additional or alternative method to improve detection of drug-related deaths.